In Situ Skin Tailoring for Myelomeningocele Repair - Khaled Aly (Egyptian Spine Journal, 2012)
Purpose: We are presenting a new technique for myelomeningocele repair in children. The currently used technique is associated with occasional difficulty of skin closure and excessive blood loss. Our modifications are meant to eliminate these difficulties.Study design: Thirty children below 6 months of age have been operated upon in the last 5 years, all having meningo/myelomeningoceles of medium to large sizes. Methods: Direct sac opening was used instead of peripheral elliptical skin incision. Skin was approximated at the end of the procedure and excess skin was shaved with scissors. Results: Our technique offers many advantages. Most importantly, is accurate skin tailoring so that ultimate usage of available skin becomes possible. Furthermore, blood loss is significantly reduced. Conclusion: The technique proposed in this work represents a valuable modification of meningo/myelomeningocele repair. (2012ESJ006)